1951
DOI: 10.1161/01.cir.3.4.492
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Disseminated Lupus Erythematosus

Abstract: Hypochromic anemia was present in 17, leukopenia in 14, elevated sedimentation rate in all cases recorded and an elevated serum globulin in 9. The diagnosis is made by summation of the clinical findings; namely, shortness of breath, joint pains, skin rash, fever, pulmonary, cardiac, and renal abnormalities, and by the laboratory findings of hypochromic anemia, albuminuria, increased sedimentation rate, elevated serum albumin, presence of lupus erythematosus cells, and by a positive skin biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1954
1954
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In patients with systemic lupus erythematosus (SLE), myocarditis may be a lifethreatening manifestation. Although in clinical studies SLE myocarditis was found in only about 9% of patients with SLE [61][62][63][64], post-mortem analyses reported a high prevalence of 57%, indicating a high prevalence of subclinical disease [65][66][67]. SLE is most common in women in their 20s and 30s, and the severity as well as the clinical manifestations of the disease differ between early and late onset [68][69][70].…”
Section: Autoimmunitymentioning
confidence: 99%
“…In patients with systemic lupus erythematosus (SLE), myocarditis may be a lifethreatening manifestation. Although in clinical studies SLE myocarditis was found in only about 9% of patients with SLE [61][62][63][64], post-mortem analyses reported a high prevalence of 57%, indicating a high prevalence of subclinical disease [65][66][67]. SLE is most common in women in their 20s and 30s, and the severity as well as the clinical manifestations of the disease differ between early and late onset [68][69][70].…”
Section: Autoimmunitymentioning
confidence: 99%
“…Although this organism was thought most likely to represent a contaminant, the patient was treated Libman-Sacks verrucous endocarditis with or without associated bacterial endocarditis occurs in as m a n y as 4 0 % of patients with systemic lupus erythematosus [26]. Griffith a n d Vural [19] however, found no constant correlation between the clinical findings and specific pathologic lesions of the heart. I n fact, an apical systolic m u r m u r was heard in only two of their six patients with endocarditis.…”
Section: Commentmentioning
confidence: 94%
“…After the introduction of corticosteroid therapy, the prevalence of autopsy-identified SLE-related myocarditis decreased from 50%–75% [19] to 25%–30% [20]. However, clinically evident lupus myocarditis is identified in less than 10% of patients, showing the high prevalence of subclinical disease [21].…”
Section: Assessing Cardiac Involvementmentioning
confidence: 99%